Digital Libraries in the New Millennium (Bangladesh Journal of Library and Information Science, 2012)
The concept of digital library is not a new one, although it is only recently that digital library is gaining prominence all over the world. This article provides a holistic understanding of digital libraries including its present context and future directions. Various technical issues ingrained in the concept of digital library also has been analysed in the article. Issues like interoperability, information retrieval, property and access control and usability also has been discussed in detail. Although digital library is a technical phenomenon, it has wider social and economic implications. The article casts a critical glance at these implications as well. In the end, ongoing international efforts in the arena of digital libraries also has been discussed. Bangladesh Journal of Library and Information Science Vol.2(1) July 2012 pp.92-102DOI: http://dx.doi.org/10.3329/bjlis.v2i1.12926